Fannia pretiosa-group (Diptera: Fanniidae) from Mexico: six new species from the Mexico Transition Zone and an identification key - Gomes, Lucas R. P.; Pedraza-Lara, Carlos (Zootaxa, 2023)
Fannia Robineau-Desvoidy is found in all biogeographic regions. The genus contains approximately 360 known species, 18 of which have been recorded from Mexico. Herein, we describe six new species in the Fannia pretiosa-group, redescribe Fannia gilvitarsis Chillcott, and provide diagnosis, habitus images, drawings of the male terminalia, and an identification key for all species of the group that occur in Mexico. All Fannia pretiosa-group species from Mexico share a similar morphology of the mid tibia, hind femur, and male terminalia.